The effect of value perceptions on luxury purchase intentions: an Angolan market perspective - Canguende-Valentim, Cláudio Félix (2023)
This study aimed to measure the effect of perceived value on purchase intention of luxury goods among Angolan consumers. It also explored the moderating effect of consumer gender. Data were collected through a survey distributed to 130 consumers in North and South Angola, employing Smart-PLS for analysis. The results indicated that perceived social value was the most important determinant of purchase intentions for luxury goods, followed by perceived individual value. The study showed that consumer gender moderated the relationship between and individual value perception and social value perception on purchase intention. The research contributes to the literature, and this study is the first empirical test of a value structure for luxury goods in the Angolan market, so it allowed to better understand the disposition of these consumers in purchase intention according to the perceived value of luxury. Theoretical and practical implications will be discussed.